PAMERAN MUSEUM SEBAGAI MEDIA KOMUNIKASI: KAJIAN BERDASARKAN PERSEPSI MODEL KAPLAN - Nurani, Indah Asikin (Berkala Arkeologi, 2009)
Exhibition at the museum is one of the communications media that can be used to present level of civilization and culture of a nation based on cultural materials on display. The essence of communication is the perception that is how visitors are able to accurately perceive the information presented in museum exhibits. Visitor perceptions of accuracy of the information depends on how curator described the encoding within the exhibitions. Formation of a person's perception of the stimulus preceded the arrest sensing nerves, then there's perception of the object, and finally the brain sends impulses through the motor nerve action. Arc sensingperception- reaction in psychology called the reflex arc. This paper describes how far the level of accuracy for the management of visitor perceptions of the exhibition at the Museum Sonobudoyo based on Kaplan's model of four variables namely coherent, easily understood, complexity, and mystery. The data was collected through questionnaires to 65 respondents.